The Performance of the Production Unit Program Ibu Kartini Semarang Vocational High School - Shagira, Rizky Yanda; Sutopo, Yeri; Syamwil, Rodia (Universitas Negeri Semarang, 2021)
Entrepreneurship program of Vocational High School (SMK) Ibu Kartini Semarang consisted of Business Centre, School of Entrepreneur, and Production unit. The implementation of the production unit faced several problems such as students’ lack of motivation in conducting industrial apprentice even though it has been scheduled in the timeline. There were gaps between industrial need and students’ output based on their specialization so that improving production units in school was crucial. This research was qualitative research that focused on evaluating the production unit program in SMK Ibu Kartini Semarang. The participants of the current study were principals, production unit staff, teachers, and production unit partners. The questionnaires, observation, and interviews were applied to gain the data. The analysis data used descriptive qualitative method with evaluation model such as context, input, process, product (CIPP). Furthermore, it was evaluated by the Glickman quadrant. The result showed that the production unit of SMK Ibu Kartini Semarang was “not effective” (++–) and the T score achieved 50 so that the improvement was needed.